Capillary electrophoresis inductively coupled plasma mass spectrometry combined with metal tag for ultrasensitively determining trace saxitoxin in seafood. Issue 3 (8th December 2016) - He, Ye; Mo, Fan; Chen, Danlong; Xu, LiangJun; Wu, Yongning; Fu, FengFu
Abstract : As one of paralytic shellfish toxins, the saxitoxin (STX) in the aqueous environment can be accumulated by most shellfish, and thus harms human health through the food chain. Therefore, it is crucial to determine trace STX in seafood samples in order to ensure the safety of seafood consumption. In this study, we developed a novel indirect method for ultrasensitively determining trace STX in seafood by using CE‐ICP‐MS together with Eu 3+ chelate labeling. We demonstrated that diethylenetriamine‐ N, N, N ′, N ″, N ″‐pentaacetic acid (DTPA) can couple with STX and simultaneously chelate with Eu 3+ to realize metallic labeling of STX, and thus realize the ultrasensitive quantification of trace STX with CE‐ICP‐MS. The proposed method has strong antiinterference ability, good stability, and extremely high sensitivity. It could be used to determine trace STX in seafood samples with an extremely low detection limit of 0.38 fmol (3.8×10 −9 M, 100 nL sample injection) and a relative standard deviation (RSD, n = 5) <7%. The success of this study provides an alternative to precise quantification of ultra‐trace STX in seafood samples, and further expands the application of ICP‐MS.